Long-Term Temporal Stability of Measured Inattention and Impulsivity in Typical and Referred Children. (January 2014) - Mayes, Susan D.; Gordon, Michael; Calhoun, Susan L.; Bixler, Edward O.
Objective: This study investigates the stability of measured inattention and impulsivity in children.Method: The Gordon Diagnostic System (GDS) assesses inattention and impulsivity and has been administered in the same manner since its 1983 publication. GDS scores were compared between the 1983 standardization sample and a recent typical sample of 445 children, 562 children with ADHD-Combined (ADHD-C) type, 235 with ADHD-Inattentive (ADHD-I) type, and 231 with autism.Results: Typical children earned a GDS composite standard score of 100, consistent with the normal mean of 100 in the 1983 standardization sample. Means for children with ADHD-C, ADHD-I, and autism were 70, 78, and 76, respectively, approximately two standard deviations below the normal mean.Conclusion: As measured by the GDS, children are no more or less inattentive and impulsive today than in 1983, suggesting that inattention and impulsivity are stable neurobiological traits largely unaffected by cultural, educational, and environmental factors.